Renal replacement therapy in heart transplant recipients - I. L. Poz; A. G. Strokov; Yu. V. Kopylova; V. N. Poptsov; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2022)
Kidney injury in cardiac transplant recipients is one of the most severe complications affecting both short- and long-term transplant outcomes. The need for renal replacement therapy (RRT) is determined not only and not so much by the degree of renal dysfunction, as by the need for correction of fluid balance and metabolic disorders. These circumstances are associated with the specificity of extracorporeal renal replacement therapy in donor heart recipients. In this review, we discuss the problems of early versus delayed initiation of RRT, anticoagulation and vascular access, advantages and disadvantages of continuous and intermittent techniques. Special attention is paid to chronic kidney injury and peculiarities of kidney transplantation in heart recipients.